2023
DOI: 10.3390/s23042059
|View full text |Cite
|
Sign up to set email alerts
|

Can Satellite Remote Sensing Assist in the Characterization of Yeasts Related to Biogeographical Origin?

Abstract: Biogeography is a key concept associated with microbial terroir, which is responsible for the differentiation and uniqueness of wines. One of the factors influencing this microbial terroir is the vegetation, which in turn is influenced by climate, soil, and cultural practices. Remote sensing instruments can provide useful information about vegetation. This study analyses the relationship between NDVI, calculated using Sentinel-2 and Landsat-8 satellite images of different veraison dates, and microbial data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…[52] have indicated that satellite multispectral imaging, through the NDVI, could potentially be used to monitor microbial terroir and yeast species richness within the vineyards. This result was confirmed in a subsequent study, finding that satellite imagery can differentiate yeasts according to their fermentative capacity and could serve as a valuable asset for managing wine differentiation and a decision-making resource for designation of origin (DO) regulators and viticulturists [53]. These novel applications could offer a non-invasive method for winemakers to improve knowledge of the microbial status of the local terroir, thus improving product distinction, quality, and added value.…”
Section: Microorganisms and Yeastsmentioning
confidence: 54%
See 1 more Smart Citation
“…[52] have indicated that satellite multispectral imaging, through the NDVI, could potentially be used to monitor microbial terroir and yeast species richness within the vineyards. This result was confirmed in a subsequent study, finding that satellite imagery can differentiate yeasts according to their fermentative capacity and could serve as a valuable asset for managing wine differentiation and a decision-making resource for designation of origin (DO) regulators and viticulturists [53]. These novel applications could offer a non-invasive method for winemakers to improve knowledge of the microbial status of the local terroir, thus improving product distinction, quality, and added value.…”
Section: Microorganisms and Yeastsmentioning
confidence: 54%
“…Agricultural management geared towards enhancing the yield quality in organic production [36,37] Detect phytochemicals in organic agriculture to facilitate the adherence to certification audits, ensuring the maintenance of safe pesticide thresholds in conventional agricultural practices [38][39][40] Increase the traceability of organic production [41] Disaster management Detect flood-affected areas [42] Identify areas affected by wildfires [43] Assess and monitor regional droughts [44] Rapid damage assessment post-disaster [45] Aid in monitoring and mapping wildfire damages and post-fire recovery [46] Microorganisms and yeasts Detect fungal infections in crops [47,48] Monitor the induction of plant defense mechanisms [49] Study the interaction of climate, topography, and soil properties with cropland [50] Identify the presence of infections in plants [51] Monitor microbial terroir and yeast-species richness within the vineyards [52] Differentiate yeasts according to their fermentative capacity and a decision-making resource for designation of origin (DO) regulators and viticulturists [53] Detect the presence of aggressive soil pathogens [54] Table 1. Cont.…”
Section: Organic Productionmentioning
confidence: 99%